FAKTOR EKSPLOITASI KAYU RAMIN (GONYSTYLUS BANCANUS MIQ) - Marolop Sinaga; Dulsalam Dulsalam; Sampe Radja Simarmata (Jurnal Penelitian Hasil Hutan, 1985)
This  investigation  is carried out  in the Central Kalimantan  and  West Kalimantan  areas at three logging companies. The purpose  of  this  investigation is to determine the  exploitation  factor  for  Gonystylus bancanus Miq.The  knowledge of  exploitation  factor will  help logging  companies in  the planning  and  control  of production. The exploitation  factor is the  ratio  of  stem volume utilized to the stem   volume that  actually  could  be utilized.   The latter represents  part  of  the stem  from  its lowest point  to its first  branch.  The part of stem  considered  utilized  is that part  which reached  the  log  pond   or  other  point   for  marketing.Exploitation  waste  in the areas of  the forest  companies  observed  ranges from  11.1%   to 21.2%.  This means  that  the exploitation  factor  ranges from 78.8%  to  88.9%.  The  average of  exploitation  waste  is 16.7%,  consisting  of parts  from stumps  2.9% and parts  from  stems  13.8%, and  hence  the  exploitation factor is 0.81.Exploitation  waste  can be kept  at a  minimum  by  better  planning  and  improving  skills  of  the  workers. The  exploitation  factors  among provincial  regions and logging companies  are not significantly.  Among  diameter  class, however,  they  differ highly significantly.  Therefore,  the exploitation factor reported here  should be used with great care.